THE ROLE OF WOMEN IN PROTECTING THE VILLAGE AND RURAL TOURISM IN TIMPAG VILLAGE - Suryawati, Dewa Ayu; Pertiwi Dewi, Si Putu Agung Ayu; Osin, Rosvita Flaviana; Anggayana, I Wayan Agus (Akademi Komunitas MAPINDO, 2021)
The area of Timpag Village , Tabanan Regency is very potential to be developed. This village has interesting natural characteristics, unique social and cultural life. In its development, it is necessary to pay attention to the existence of the role of woman. The purpose of this study was to determine the role of women in protecting villages and tourist villages in Timpag village. This research is a type of qualitative research that uses data collection techniques with direct observation to the research location (observation), in-depth interviews, distributing questionnaires, and using literature studies. This study looks at the involvement of women in tourism activities, political empowerment motivates, social empowerment, economic empowerment. Women in the Timpag village not only gain economic benefits but also foster a sense of pride in their local culture. The women in Timpag village are actively involved in the Family Welfare Development group, which is a community organization that empowers women to participate in Indonesia's development. Keywords: Role, Woman, Timpag Village